Fetal Alcohol Spectrum Disorder Prevalence Estimates in Correctional Systems: A Systematic Literature Review - Popova, Svetlana (Can J Public Health, 2011)
Objectives: The objective of this study was to conduct a systematic search of the literature for studies that estimated the prevalence/incidence of Fetal Alcohol Spectrum Disorder (FASD) in correctional systems in different countries and, based on these data, to estimate a) the number of people with Fetal Alcohol Syndrome (FAS)/FASD within the criminal justice system population, and b) the relative risk of becoming imprisoned for individuals with FAS/FASD compared with those without FAS/FASD. Method: A systematic world literature review of published and unpublished studies concerning the prevalence/incidence of FASD in correctional systems was conducted in multiple electronic bibliographic databases. Synthesis: Very little empirical evidence is available on the prevalence of FASD in correctional systems. There were no studies estimating the prevalence/incidence of FASD in correctional systems found for any country other than Canada and the USA. The few studies that have identified incarcerated individuals with FASD estimate that the number of undiagnosed persons in correctional facilities is high. Based on available Canadian data, this study estimates that youths with FASD are 19 times more likely to be incarcerated than youths without FASD in a given year. Conclusion: More studies investigating the prevalence/incidence of alcohol-affected people in the criminal justice system are required. There is an urgent need to raise awareness about the prevalence and disabilities of individuals with FASD in the criminal justice system and about appropriate responses. The criminal justice system is an ideal arena for intervention efforts aimed at the rehabilitation and prevention or reduction of recidivism in this unique population.